2004
DOI: 10.1111/j.0001-6349.2004.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Episiotomy and perineal tears presumed to be imminent: randomized controlled trial

Abstract: Avoiding episiotomy at tears presumed to be imminent increases the rate of intact perinea and the rate of only minor perineal trauma, reduces postpartum perineal pain and does not have any adverse effects on maternal or fetal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 17 publications
0
61
0
7
Order By: Relevance
“…(14) An investigation conducted in Germany compared two proposals of episiotomy use in primip-arous women who underwent spontaneous vaginal delivery and vacuum extraction delivery: (1) restricted use (only for fetal indication) and (2) liberal use (both fetal indication and eminent perineal laceration); the study found no difference in hemoglobin variation between the pre and postpartum periods between women managed according to either of the two proposals. (15) Episiotomy and perineal trauma repair are the two surgical procedures most conducted by obstetricians. In Brazil the episiotomy rate is 71.6%, although current efforts aim to reduce it to 10%.…”
Section: Discussionmentioning
confidence: 99%
“…(14) An investigation conducted in Germany compared two proposals of episiotomy use in primip-arous women who underwent spontaneous vaginal delivery and vacuum extraction delivery: (1) restricted use (only for fetal indication) and (2) liberal use (both fetal indication and eminent perineal laceration); the study found no difference in hemoglobin variation between the pre and postpartum periods between women managed according to either of the two proposals. (15) Episiotomy and perineal trauma repair are the two surgical procedures most conducted by obstetricians. In Brazil the episiotomy rate is 71.6%, although current efforts aim to reduce it to 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Este resultado coincide con otros estudios consultados (29,30) , incluso con los que valoran el test de Ápgar como medida para determinar el bienestar fetal (7,(10)(11)(12)30,31) . Por tanto, la justificación del uso de la episiotomía para la reducción de la morbilidad fetal y neonatal no tendría sustento.…”
Section: Nº 35 Julio 2014unclassified
“…In fact, an episiotomy is associated with more pain, sexual problems, and incontinence after birth (Goer et al, 2007;Hartman et al, 2005;Klein et al, 1994;Renfrew, Hannah, Albers, & Floyd, 1998). Also, episiotomies done to ''prevent'' tears that the provider thinks are about to happen actually cause more tears (Dannecker et al, 2004). The episiotomy rate can be safely lowered to 10% or even lower (Goer et al, 2007).…”
Section: Episiotomymentioning
confidence: 99%